2021
DOI: 10.1109/tit.2021.3114142
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Causal Rate-Constrained Sampling for a Class of Continuous Markov Processes

Abstract: Consider the following communication scenario. An encoder observes a stochastic process and causally decides when and what to transmit about it, under a constraint on bits transmitted per second. A decoder uses the received codewords to causally estimate the process in real time. The encoder and the decoder are synchronized in time. We aim to find the optimal encoding and decoding policies that minimize the end-to-end estimation mean-square error under the rate constraint. For a class of continuous Markov proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(83 reference statements)
0
6
1
Order By: Relevance
“…Then, threshold policies are shown optimal in this case, in which a new sample is acquired only if the expected age-penalty by the time it arrives surpasses a certain value. This paper extends [38] (and the related studies in [39,40]) to multiple OU processes.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Then, threshold policies are shown optimal in this case, in which a new sample is acquired only if the expected age-penalty by the time it arrives surpasses a certain value. This paper extends [38] (and the related studies in [39,40]) to multiple OU processes.…”
Section: Introductionmentioning
confidence: 60%
“…Our recent work in [39] also focuses on characterizing the relationship of MSE and AoI, yet with the additional presence of coding and quantization. Reference [40] shows the optimality of threshold policies for tracking OU processes under rate constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Rabi et al [8] formulated the estimation of the scalar Wiener and scalar Ornstein-Uhlenbeck processes as an optimal multiple stopping time problem by discarding the signaling effect, and showed that the optimal triggering policy is symmetric threshold. Guo and Kostina [9] addressed the estimation of the scalar Wiener and scalar Ornstein-Uhlenbeck processes in the presence of the signaling effect, and obtained a result that matches with that in [8]. They also looked at the estimation of the scalar Wiener process with fixed communication delay in the presence of the signaling effect in [10], and obtained a similar structural result.…”
Section: Introductionmentioning
confidence: 86%
“…There are multiple works that are closely related to our study [5][6][7][8][9][10][11]. In these works, optimal triggering policies were characterized in settings that are different from ours.…”
Section: Introductionmentioning
confidence: 99%
“…packet-erasure channel in [5], [6], remote estimation of a scalar Markov process with symmetric noise distribution over an ideal channel in [9], remote estimation of a scalar autoregressive Markov process with symmetric noise distribution over an ideal channel, an i.i.d. packet-erasure channel, and a Gilbert-Elliott packeterasure channel in [10]- [12], remote estimation of the scalar Wiener and scalar Ornstein-Uhlenbeck processes over an ideal channel and a fixed-delay channel in [13], [14], remote estimation of the scalar Wiener process over a random-delay channel in [15], remote estimation of multiple random variables with arbitrary distributions over a collision channel in [16], [17], remote estimation of multiple random variables with arbitrary distributions over unicast and broadcast channels in [18], and remote estimation of two Gaussian random variables over a multi-access channel in [19]. These studies established certain characteristics such as a symmetric, asymmetric, or threshold structure of the optimal scheduling policy with respect to the estimation discrepancy.…”
Section: A Related Workmentioning
confidence: 99%